Optimization of antibiotic dosing regime through pharmacokinetics/ pharmacodynamics integration: a review - Alexsandra Felix, Larissa (2024)
The indiscriminate use of antimicrobials led to the emergence of antimicrobial resistance (AMR), so the rational use of these medications becomes extremely necessary. Thus, an alternative is the use of pharmacokinetic/pharmacodynamic (PK/PD) integration, a tool used in human and veterinary medicine, to determine dosing regimen optimization. Optimizing the dosage regimen makes it possible to establish therapies with greater precision and probability of clinical success, in addition to minimizing toxicity and the spread of antimicrobial resistance. PK/PD integration studies are included in the European Medicines Agency (EMA) guidelines for evaluating medical products; however, this tool needs to be more widespread. Additionally, in 2015, the World Health Organization (WHO) established optimizing antimicrobial doses as one of the five critical points to help reduce the spread of AMR, so PK/PD integration can be used for this purpose. Therefore, this review aimed to elucidate the aspects of PK/PD integration in the selection and optimization of dosing regimens to increase awareness of their development and use by veterinary practitioners.